Annual Report on the Big Data of New Energy Vehicle in China (2023) - Wang, Zhenpo (Springer Nature, 2024)
This open access book, based on static indicators and dynamic big data from local electric vehicles, is the first research annual report on the Big Data of New Energy Vehicles (NEVs) in China. Using the real-time big data collected by China's National Monitoring and Management Platform for NEVs, this book delves into the main annual technological progress of NEVs, the vehicle operating characteristics, and it also anticipates the trend of NEVs industry. Various graphs and charts and detailed data this book will familiarize readers with the operation characteristics and practical application of China's NEVs industry and popularize the concept of automobile electrification. Besides, this book also makes an objective evaluation of the current situation and technological improvement of China's NEVs industry, presenting sensible suggestions for the development of the industry. This book is written for government staff, researchers, college staff, and technical staff of automobile and spare parts enterprises, which serves as an important reference for the decision-making of government departments and strategic decisions of automotive companies.